Pregnancy Outcomes among Girls Impacted by Commercial Sexual Exploitation - Barnert, Elizabeth S. (Acad Pediatr, 2019)
OBJECTIVE: We measured pregnancy rates and pregnancy outcomes among girls with histories of commercial sexual exploitation (CSE), and then quantified the associations between the outcome of pregnancy with: a) girls’ exposure to childhood adversity, and b) their behavioral health. This is the largest study of pregnancy outcomes and associated factors among girls impacted by CSE in the United States. METHODS: We reviewed court files of participants in a juvenile specialty court for youth impacted by CSE, between 2012 and 2016. We collected data on pregnancy, health, and social factors. Data were updated through 2018 and descriptive statistics were calculated. Two-sample tests for equality of proportions explored associations between pregnancy with adverse childhood experiences and the girls’ behavioral health profiles. RESULTS: Among the 360 biological females, 31% had ever been pregnant. Of the girls ever pregnant, 18% had multiple pregnancies. Outcomes for the 130 reported pregnancies were: 76% live births; 13% therapeutic abortions; 5% miscarriages or stillbirths; and 6% of pregnancies were ongoing at case closure. Parental incarceration and histories of maternal substance abuse were both associated with pregnancy. CONCLUSIONS: High pregnancy rates among girls with histories of CSE suggest the importance of applying a reproductive justice approach to deliver reproductive education, family planning services, pre-natal care, and parenting support to girls impacted by CSE.